50-Years of hybrid pigeonpea research and development: The gains and hiccups - Saxena, K.B.; Choudhary, A.K.; Dalvi, V.A.; Saxena, R.K.; Kumar, R.V.; Chauhan, Y.S.; Srivastava, R.K.; Kumar, C.V.S.; Hingane, A.J.; Gangashetty, P.; Sultana R.; Srivastava, N. (2025)
To smash the low-yield plateau in pigeonpea [Cajanus cajan (L.) Millsp.], a hybrid breeding programme was launched in 1974. Now 50 years of its research and development have been completed and this manuscript takes stock of its accomplishments, hiccups, present status, and future plans. This programme got wings when pigeonpea breeders successfully bred cytoplasmic nuclear male sterility (CMS) systems, and following this, six hybrids with 30- 50% standard heterosis were released. To realize the true value of hybrids and commercialize them, a strong seed quality control system is necessary. Traditionally, the genetic truthfulness of hybrid seeds is assessed through a standard “Grow-out Test (GoT)”. This involves sowing the freshly harvested hybrid seeds and assessing their progenies for a dominant quality determining phenotypic marker. Pigeonpea, being a short-day species, its plants flower only when the day length is around 10-11 h. Since the pigeonpea crop is harvested under increasing photo-periods, the sowing of hybrid seeds, soon after the harvest will not produce flowers under the prevailing long summer days and this will not allow the required assessment of their progenies. Due to this sole reason, the GoT could not be applied to the released photo-sensitive hybrids. This leaves breeders with no option except to look for some alternative seed quality control system. In this context, the application of molecular markers to discriminate between true hybrids and off-types appeared to be the right way. At present molecular marker-based quality testing kits are available to assist seed producers in controlling the purity of hybrid seeds. We believe that in future a follow-up hybrid promotional programme with new technologies would help in breaking the low-yield plateau and enhance the national pigeonpea production.